Determining the possibility of using non destructive testing (NDT) to detect the deterioration of wood products / Liew Yit Lian … [et al.]. - Liew, Yit Lian; Liew, Fiji Kiew; Awang Hashim, Dayang Maryani (2010)
Dynamic modulus of Elasticity (MOE) is one of the widely used characteristics for the evaluation of wood strength. MOE of five selected tropical species, which were Acacia mangium, Lithocarous sp., Cotylelobium melanoxylon, Paraserianthes falcalaria and Elmerrillia mollis were studied using the free-free flexural vibration method, which is one of the NDTs. The decrease or increase of MOE indicated that NDT is possible to be used to detect the deterioration of wood caused by the natural surroundings. The result had also shown that NDT was to be used successfully to trace the changes of MOE. The relationship between MOE and the temperature, rainfall and humidity were studied and MOE was found not significantly correlated with the temperature, humidity and rainfall.